Circulating plasma cells: from basic mechanisms to clinical applications - Wang, Pingping; Su, Nan; Yan, Xiaojing; Xu, Feng; Zhang, Yan (Frontiers in Immunology, 2025)
Circulating plasma cells (CPCs) represent an accessible subset of antibody-secreting cells that provide valuable insights into immune activation and regulation. This review presents the first comprehensive synthesis of CPC biology, with a particular focus on the mechanisms governing their generation under physiological conditions and the distinct pathways that drive their formation within tumor microenvironments. We further summarize the broader clinical relevance of CPCs as potential biomarkers across infections, autoimmune diseases, and plasma cell disorders. With the rapid advancement of liquid biopsy technologies, CPC detection has garnered increasing attention in clinical practice. Here, we evaluate current and emerging methods for CPC detection, highlighting their respective advantages and limitations. Finally, we discuss the translational potential of CPCs and outline future research directions to support more precise diagnosis and treatment strategies in CPC-associated conditions.